Desempenho de linhas de transmissão frente a descargas atmosféricas: desenvolvimento de ferramenta computacional e análise de medidas mitigatórias em regiões com restrições ambientais. - Lima, Vitor Rocha de Almeida Rego (2020)
Lightning strikes represent the main factor responsible for non-scheduled transmission lines outages. The evaluation of the performance of the transmission lines against lightning strikes is fundamental and represents, therefore, an area of research of great relevance for the electrical system. Due to the complexity and the simultaneous performance of several elements of the system, the tools traditionally used to measure the performance of a transmission line at the time of the incidence of a lightning flash present approximations and limitations that can deviate the results of the real phenomenon. In this context, the present work presents a computational tool capable of simulating the overvoltages obtained during an lightning flash in a structure and presenting the estimated number of outages of the transmission line, including an accurate modeling of the grounding system. An extensive bibliographic review is made on the main works published in the technical literature regarding the modeling of each of the elements needed for the elaboration of this tool. Finally, the computational tool is used to obtain several results of practical interest, including simulations of real systems with different grounding systems topologies installed in areas with environmental restrictions, as well as unconventional mitigation measures such as the installation of additional ground wires.